Evaluating Student Insights, Attitudes, and Understandings on Green Accounting within the Green Economy Framework - Hasinah, Hasinah; Rismawati, Rismawati; Supri, Zikra (E-Jurnal Akuntansi; Vol 33 No 10 (2023), 2023)
This research aims to assess students' knowledge, attitudes, and perceptions regarding green accounting in the context of the green economy. Previous studies have predominantly focused on green accounting within corporations, while student perspectives are pivotal for the future of sustainable economics. Using a quantitative approach, this study involved 133 purposively sampled respondents. Multiple linear regression was used for data analysis. This research offers insight into how students' perceptions and attitudes towards green accounting can impact sustainable practices' adoption. It's among the few studies addressing students, future key players in the green economy. The findings contribute significantly to green accounting education and training. Moreover, it can aid policymakers and practitioners in designing more effective educational programs. Keywords: Knowledge; Attitude; Perception; green accounting; economics.